The impact of environmental information disclosure on an organization’s environmental performance - a case study Condor Electronics - drici, ridha; lassag, hizia (Journal of Research in Finance and Accounting, 2024)
This study investigates the influence of environmental information disclosure on the environmental performance of organizations, focusing on both internal and external influencing factors. A descriptive and analytical method was applied, with data collected from 52 questionnaires and analyzed via SPSS software. The findings indicate that environmental disclosure has a significant positive effect on environmental performance. These results emphasize the critical role of transparency and the need for policies that encourage disclosure to support sustainable environmental objectives